Spontaneous decolonization during hospitalization in intensive care unit patients colonized by extended-spectrum beta-lactamase-producing Enterobacterales. Issue 3 (November 2020) - Duployez, C.; Wallet, F.; Rouzé, A.; Nseir, S.; Kipnis, E.; El Kalioubie, A.; Dessein, R.; Loïez, C.; Le Guern, R.
Summary: This study aimed to analyse the frequency of occurrence of spontaneous decolonization in intensive care unit patients colonized by extended-spectrum beta-lactamase-producing Enterobacterales (ESBL-E) in order to assess the added value of continuing weekly ESBL-E rectal carriage screening in these patients. In total, 49, 468 weekly rectal screening samples taken from 20, 846 patients over 12 years were included. Among the 4280 ESBL-E carriers, only 109 patients (2.5%) could be considered decolonized at the end of their hospitalization with at least three consecutive negative samples. Overall, 7957 samples (16.1%) were requested for patients already identified as ESBL-E carriers. Avoiding unnecessary weekly screening following positive ESBL-E colonization results could decrease nursing and laboratory work loads.